Serum Mineral Profile in Holstein Friesian Crossbred Cows with Normal and Low Solids-not-fat Milk Syndrome - Nyamagonda, Hanamanta; Swamy, Muniyappa N.; Kalmath, Gurubasayya P.; Rao, Suguna; Ramesh, Pujari T.; Isloor, Srikrishna; Veena, Malavalli P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A study was undertaken to compare the serum mineral profile in Holstein Friesian crossbred cows with low solids-not-fat (SNF) syndrome  and normal SNF content during 4th and 8th week of 3rd and 5th lactations. A total of 24 cows were selected for the present study and  based on the SNF content in their milk, the animals were divided into four groups, viz., Group I (>8.5% SNF milk in 3rd lactation), Group  II (< 8.5% SNF milk in 3rd lactation), Group III (>8.5% SNF milk in 5th lactation) and Group IV (
Keywords: Comparative study; Crossbred cows; Normal SNF; Serum minerals; Low SNF Syndrome